The determinants of FDI and Its impact on economic growth: A comparative study - xu, hanglu (2016)
This paper investigates the determinants of FDI and the effect of FDI on economic growth based on the panel data of 112 countries in Asia, Latin America and Sub-Saharan Africa over the period 1980-2014. The results show that higher GDP, trade balance and domestic investment could attract more FDI. FDI inflow could promote economic growth, but this positive effect is less for country with better infrastructure and financial development. From sub-sample analysis, the positive effect of FDI on economic growth is less for countries with better infrastructure and financial development in Asia, whereas the positive effect of FDI on economic growth is less for countries with lower technology level, more government consumption, and better financial development in Sub-Saharan Africa. Finally, the positive effect of FDI on economic growth is not restrained by any condition in host countries in Latin America.